De novo duplication of the 7q11 leads to q22 region. Issue 6 (December 1983) - Kardon, N B; Pollack, L; Davis, J; Broekman, A; Krauss, M
Abstract : A patient with de novo partial trisomy for the 7q11 leads to 7q22 region as defined by methotrexate high resolution banding is described. he presented with delayed growth and development and characteristic physical features. These consisted of frontal bossing, prominent metopic suture, almond shaped eyes, enophthalmos, large, low set, posteriorly rotated ears, long philtrum, narrow upper lip, high arched palate, and a short neck. Specific genitourinary anomalies were noted.